Pengaruh Social Media Marketing Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada PT Mahakarya Kemasan Digital - Galang Kisowo (Jurnal of Management and Social Sciences, 2023)
This study aims to determine the effect of social media marketing variables (X1) and service quality (X2) on purchasing decisions (Y) at PT Mahakarya Paket Digital. This type of research is quantitative research. Data collection techniques used are primary data and secondary data. The sample selection used the accidental sampling method, a sample of 55 respondents at PT Mahakarya Paket Digital. The analysis technique used is validity test, reliability test, classic assumption test, multiple linear regression analysis, t test, F test and coefficient of determination test. From the results carried out in the study, it showed that product quality (X1) and price (X2) variables on customer satisfaction (Y) at PT Mahakarya Kemasan Digital. The results of the study obtained a linear regression equation for social media marketing variables that have a partially significant effect on purchasing decisions. Quality of Service has a significant effect on purchasing decisions partially. The results of the Social Media Marching F test and Service Quality have a simultaneous and significant effect on Purchasing Decisions at PT Mahakarya Paket Digital.